Changes in Serum Inflammatory Markers and in Clinical Periodontal Condition After Non-Surgical Periodontal Treatment in Hypertensive Patients - Francina María Escobar Arregoces; Nelly S. Roa; Juliana Velosa-Porras; Lina Velásquez Rodríguez; María José Merchan; Jean Carlos Villamil Poveda; Liliana Otero; Álvaro J. Ruiz; Catalina Latorre Uriza (Biomedicines)
Background: Chronic inflammatory disorders, such as periodontitis, may contribute to pro-hypertensive inflammation. Objectives: This study aimed to analyze changes in parameters for periodontitis, such as periodontal inflamed surface area (PISA) and serum inflammatory markers, following non-surgical periodontal treatment in hypertensive patients. Methods: A quasi-experimental pre-and-post study was conducted, involving 42 controlled hypertensive patients with periodontitis. The patients underwent periodontal assessment and tests, including complete blood count, glucose, triglycerides, HDL-C, LDL-C, and serum levels of inflammatory biomarkers. All patients received scaling and root planning treatment in a single session and were reevaluated one month after the treatment. Results: Post-treatment evaluations showed significant improvements in periodontal inflammation parameters, such as pocket depth, attachment level, bleeding on probing, and biofilm percentage, with statistically significant differences (p < 0.001). There were decreases in serum VEGF levels (p < 0.001) and reductions in PISA associated with declines in cytokine levels such as IL-10, IL-6, IL-12p70, IL-17A, and VEGF. PISA for IL-6 and IL-10 had a positive correlation before periodontal treatment and with IL-1β and IL-10 after treatment. Conclusions: Hypertensive patients with periodontitis who underwent non-surgical periodontal treatment showed improvements in their periodontal condition, a decrease in cytokine levels such as VEGF, and reductions in PISA associated with declines in cytokines such as IL-10, IL-6, IL-12p70, IL-17A, and VEGF. These findings confirm the role of inflammation in hypertensive patients with periodontitis.